Network effects on the internationalization process of Icelandic Software Firms - Tryggvi Jónsson 1978- (2014)
Background Changes in the international market environment have allowed software firms from small economies to reach market niches across the globe. The use of network relationships can help firms to skip stages in the internationalization processes and link together resources or reach market niches that are not available domestically. Problem Many studies have pointed out the influence of network relationships on the internationalization decisions of SMEs. The market for software in Iceland is limited which forces its software firms to search for clients in other markets so they can recoup their investments. Purpose The purpose of this thesis is to examine how small to medium sized Icelandic software companies move to international markets and how network relationships affected their decisions. Method This thesis uses a qualitative research design by applying a multiple case-study approach. Five internationalized Icelandic software SMEs were interviewed. Data were collected by a semi-structured interview guide supported with secondary data. Collected data were categorized with analysis of each case. A cross-case analysis was performed to find out differences or similarities between the case-firms. Findings The case-firms focused on product strategy and went to markets where opportunities were to be found. The common theme was to enter first geographically close markets with psychic similarities and then gradually move to more distant ones. Network relationships were mainly used to support further expansion or gain the confidence of potential clients either within markets where there was already presence or in more distant ones. Keywords Internationalization, networks, software firms, international new ventures, Uppsala model.